Cosmogenic nuclide data from glacial deposits along the Liv Glacier coast - Stone, John (U.S. Antarctic Program (USAP) Data Center, 2019)
This data set contains measurements of cosmic-ray-produced Be-10 in quartz from glacial erratics and bedrock at sites along and adjacent to Liv Glacier and Amundsen Glacier in the southern Transantarctic Mountains. Samples were collected during the 2016-17 and 2017-18 field seasons working from remote camps along the coast. Locations were determined by hand-held GPS. Elevations are based on barometric altimetry corrected for daily drift and referenced to precise (geodetic) GPS benchmarks established over a range of altitudes at each site. Horizon geometry and the resulting topographic shielding of the cosmic ray flux was determined from vertically-oriented full-sky (fisheye) photographs at each sample location. Samples were processed at the University of Washington Cosmogenic Nuclide Laboratory using established procedures for mineral separation, dissolution, beryllium extraction and purification, described at http://depts.washington.edu/cosmolab/chem.shtml. Beryllium isotope ratios were measured at the Lawrence Livermore Center for Accelerator Mass Spectrometry (LLNL-CAMS) relative to the KNSTD-Be-01-5-4 standard, assuming a standard Be-10/Be-9 ratio of 2.851E-12 (07KNSTD normalization). Data are reported as input for the online CRONUS cosmogenic nuclide calculator (V3, current at the time of submission in November 2019). Exposure ages can be obtained by entering the data into the CRONUS calculator, at: http://hess.ess.washington.edu/math/v3/v3_age_in.html . Data for each sample consists of two lines of input parameters, as follows: {Sample_name, Latitude (DD), Longitude (DD), Altitude (m asl), Scaling_function, Thickness (cm), Density (g/cm^3), Horizon_correction, Erosion_rate (cm/yr), Year_sampled} {Sample_name, Nuclide (in this case Be-10), Target_mineral (quartz), Be-10_concentration (atom/g), Error_Be-10_concentration (atom/g), Normalization} Further information about the V3 input format is given at: http://hess.ess.washington.edu/math/docs/v3/v3_input_explained.html